NMR-based metabolomics to determine acute inhalation effects of nano- and fine-sized ZnO particles in the rat lung. Issue 7 (8th August 2016) - Lee, Sheng-Han; Wang, Ting-Yi; Hong, Jia-Huei; Cheng, Tsun-Jen; Lin, Ching-Yu
Abstract: Zinc oxide (ZnO) particles induce acute occupational inhalation illness in humans and rats. However, the possible molecular mechanisms of ZnO particles on the respiratory system remain unclear. In this study, metabolic responses of the respiratory system of rats inhaled ZnO particles were investigated by a nuclear magnetic resonance (NMR)-based metabolomic approach. Male Sprague–Dawley rats were treated with a series of doses of nano-sized (35 nm) or fine-sized (250 nm) ZnO particles. The corresponding control groups inhaled filtered air. After 24 h, bronchoalveolar lavage fluid (BALF) and lung tissues were collected, extracted and prepared for 1 H and J-resolved NMR analysis, followed by principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA). PCA and PLSDA models from analysis of BALF and hydrophilic lung NMR spectra demonstrated that dose response trends were restricted to the 250 nm ZnO particle exposure group and were not observed in the 35 nm ZnO particle exposure group. Increased isoleucine and valine, as well as decreased acetate, trimethylamine n -oxide, taurine, glycine, formate, ascorbate and glycerophosphocholine, were recorded in the BALF of rats treated with moderate and high dose 250 nm ZnO exposures. Decreases in taurine and glucose, as well as an increase of phosphorylcholine-containing lipids and fatty acyl chains, were detected in the lung tissues from 250 nm ZnO-treated rats. These metabolic changes may be associated with cell anti-oxidation, energy metabolism, DNA damage and membrane stability. We also concluded that a metabolic approach provides more complete measurements and suggests potential molecular mechanisms of adverse effects.